S2k guideline: Diagnosis and treatment of chronic pruritus - Ständer, Sonja; Zeidler, Claudia; Augustin, Matthias; Darsow, Ulf; Kremer, Andreas; Legat, Franz J.; Koschmieder, Steffen; Kupfer, Jörg; Mettang, Thomas; Metz, Martin; Nast, Alexander; Raap, Ulrike; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Pruritus is a cross-disciplinary leading symptom of numerous diseases and represents an interdisciplinary diagnostic and therapeutic challenge. In contrast to acute pruritus, chronic pruritus (CP) is a symptom of various diseases that is usually difficult to treat. Scratching and the development of scratch-associated skin lesions can alter the original skin status. In the presence of an itch-scratch-cycle, even secondary diseases such as chronic prurigo can develop. Chronic pruritus leads to considerable subjective suffering of those affected, which can result in restrictions on the health-related quality of life such as sleep disturbances, anxiety, depressiveness, experience of stigmatization and/or social withdrawal up to clinically relevant psychic comorbidities. Medical care of patients should therefore include (a) interdisciplinary diagnosis and therapy of the triggering underlying disease, (b) therapy of the secondary symptoms of pruritus (dermatological therapy, sleep promotion, in the case of an accompanying or underlying psychological or psychosomatic disease an appropriate psychological-psychotherapeutic treatment) and (c) symptomatic antipruritic therapy. The aim of this interdisciplinary guideline is to define and standardize the therapeutic procedure as well as the interdisciplinary diagnosis of CP. This is the short version of the updated S2k-guideline for chronic pruritus. The long version can be found at www.awmf.org.
CRIS-Team Scopus Importer:2022-10-28